Study of Physical Properties on Spodosols in Eucalyptus Plantation Area at PT. Wirakarya Sakti - Dhitia Sukmarian; wiskandar wiskandar; Mohd Zuhdi; Ajidirman Ajidirman (Agrosains : Jurnal Penelitian Agronomi, 2024)
Spodosols are widely distributed across Indonesia, covering approximately 2.16 million hectares, presenting significant potential for utilization as industrial forest plantation land, heavily reliant on its physical properties. The selection of the type of HTI plants to be cultivated depends on their adaptability. Eucalyptus is one plant known for its good adaptability to less fertile soil. This research was conducted on the land of PT. Wirakarya Sakti for 3 months, from February to April 2023, located in District 1, Betara District, Tanjung Jabung Barat Regency, Jambi Province. The aim of the research is to investigate the impact of land use planted with Eucalyptus compared to conservation forest on the physical properties of the soil. The research utilized a field survey method covering an area of approximately 326.4 hectares and the determination of points and sample collection using the stratified random sampling method. Samples were taken at locations including the conservation forest and land planted with Eucalyptus aged 1, 2, and 3 years, with 6 samples taken at depths of 0-30 cm and 30-60 cm, totaling 48 samples. Observed variables included soil texture, organic matter, bulk density, total pore space, moisture content, and permeability. The research results indicate that the physical properties of Spodosol soil include high soil volume weight due to the presence of an albic horizon in the upper layer and a spodic horizon in the lower layer, as well as high organic carbon content in the spodic horizon